Predicting Renal Cell Carcinoma Subtypes and Fuhrman Grading Using Multiphasic CT-Based Texture Analysis and Machine Learning Techniques - Amit Gupta; Sanil Garg; Neel Yadav; Rohan Raju Dhanakshirur; Kshitiz Jain; Rishi Nayyar; Seema Kaushal; Chandan J. Das (Indian Journal of Radiology and Imaging)
Objectives The aim of this study is to evaluate computed tomography texture analysis (CTTA) on multiphase CT scans for distinguishing clear cell renal cell carcinoma (ccRCC) from non-ccRCC and predicting Fuhrman's grade in ccRCC using open-source Python libraries.